Yolk utilization in a mangrove crab Sesarma brockii (de man) - Kannupandi, T; Vijayakumar, G; Soundarapandian, P (Indian Journal of Fisheries, 2011)
It was observed that in Sesarma brockii water and ash contents of the eggsincreased, while the biochemical constituents like protein, carbohydrate andlipid decreased with embryonic development. This reflects the depletion of energy sources in the egg as shown by reduction in dry weight (28.530 to 10.720 cal. g dry weight). The cumulative yolk utilization efficiencies of the egg during development were 65.99, 19.22, 23.11, 18.64, 18.03 and 77.95% for the dry matter, organic substances, energy content, protein, carbohydrate and lipid contents respectively. The gross efficiency and energy loss during the embryonic development was 76.88 and 23.12% respectively. Results of the present investigation clearly indicates that lipid is the main food reserve used for embryonic development.